Indonesia’s Imperative Asset Forfeiture Bill to Combat Illicit Enrichment - Tri Indah Sakinah; Thoriq Ziyad Rahman; Alfarezi Setiawan (Universitas Negeri Semarang, 2023)
Corruption poses a severe threat to Indonesia’s socio-economic development and political stability. Illicit enrichment, particularly prevalent among public officials and individuals in positions of power, perpetuates this issue by allowing for the unlawful accumulation of wealth through corrupt practices. The absence of comprehensive legislation targeting illicit enrichment has hindered effective deterrence and recovery efforts. The proposed Asset Forfeiture Bill emerges as a crucial initiative aimed at addressing these challenges. This paper underscores the pressing need for the Asset Forfeiture Bill within Indonesia’s anti-corruption framework. By enabling the confiscation of assets acquired through corrupt means, the bill promises to disrupt the incentive structure that drives corruption. It fills existing legal gaps that have previously hindered asset recovery and underscores accountability among public officials. Moreover, the bill is poised to strengthen Indonesia's legal arsenal against corruption, signaling a commitment to transparency and governance reform. Implementation of the Asset Forfeiture Bill is expected to enhance public trust in governmental institutions and foster a more conducive environment for sustainable development. By deterring illicit enrichment and recovering misappropriated public resources, Indonesia can bolster its efforts towards achieving integrity in governance and fostering economic growth. This paper advocates for the prompt adoption and effective implementation of the Asset Forfeiture Bill as a critical step towards combating corruption and promoting a fairer and more equitable society in Indonesia.